2022
DOI: 10.2147/jir.s344857
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Autophagosomes from Alveolar Macrophages Exacerbate Acute Respiratory Distress Syndrome by Releasing IL-1β

Abstract: Purpose Activated alveolar macrophages (AMs) secrete extracellular vesicles and particles to mediate the inflammatory response in the acute respiratory distress syndrome (ARDS) although the underlying mechanisms are poorly understood. This study investigated whether secretory autophagosomes (SAPs) from AMs contribute to the inflammation-mediated lung injury of ARDS. Methods We first isolated SAPs from cell culture supernatants of RAW264.7 cells and AMs and quantified In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The production of pro-inflammatory cytokines is an important feature of ARDS, and therapeutic targeting of these cytokines can ameliorate ARDS progression ( Rubenfeld et al., 2005 ; Vanden Berghe et al., 2014 ). We demonstrated that AM-derived SAPs contributed to the overwhelming inflammation of ARDS via secretion of IL-1β ( Xu et al., 2022 ). Thus, it is reasonable to assume that the MiR-199a-3p antagomir could have a protective function by modulating SAP secretion, which implies that the MiR-199a-3p antagomir may be a curative candidate for the treatment of ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of pro-inflammatory cytokines is an important feature of ARDS, and therapeutic targeting of these cytokines can ameliorate ARDS progression ( Rubenfeld et al., 2005 ; Vanden Berghe et al., 2014 ). We demonstrated that AM-derived SAPs contributed to the overwhelming inflammation of ARDS via secretion of IL-1β ( Xu et al., 2022 ). Thus, it is reasonable to assume that the MiR-199a-3p antagomir could have a protective function by modulating SAP secretion, which implies that the MiR-199a-3p antagomir may be a curative candidate for the treatment of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…We collected secretory autophagosomes in accordance with the methods published previously ( Xu et al., 2022 ). In order to remove debris, the cell culture supernatants or bronchoalveolar lavage fluid samples were acquired and centrifuged at 400× g for 5 min at first; then, we collected the supernatants for centrifugation of 12,000× g for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes/macrophages are the predominant cell type that secretes IL-1β. In pulmonary inflammatory diseases such as lung infection, 32 pulmonary fibrosis, 33 asthma, 34 and ALI, 35 a high number of IL-1β produced by AMs correlates strongly with disease severity. We found that iNOS and IL-1β mRNA and protein expression were extremely high in the LPS-treated AMs, and the knockdown of C/EBPβ significantly altered this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting aspect is the role of secretory autophagosomes (SAPs), double-membrane vesicles which can be regarded as EVs and exacerbate lung injury. SAPs were secreted by LPS-treated AMs and their intratracheal administration induced lung injury through IL-1β secretion [ 111 ]. EVs extracted from BALF of mice treated with intratracheal LPS showed an increased expression of miRNA-466.…”
Section: Role Of Extracellular Vesicles In Sepsis-associated Ardsmentioning
confidence: 99%